Glossy privet (Ligustrum lucidum) invasion decreases Chaco Serrano forest bird diversity but favors its seed dispersers - Bellis, Laura Marisa; Astudillo, Agustina; Gavier Pizarro, Gregorio Ignacio; Dardanelli, Sebastian; Landi, Marcos Alejandro; Hoyos, Laura (Springer, 2020)
Glossy privet (Ligustrum lucidum) is an aggressive invasive plant that replaces native forests and forms dense stands without understory in central Argentina. However, the consequences of these changes in terms of vegetation structure and composition in bird communities are unknown. Our goal was to understand how the effects of glossy privet invasion-induced habitat changes vary among bird species that differ in resource requirements (e.g., fruit supply, vegetation structure) and how these responses may in turn interact with the invasion process. We compared the avian–habitat relationships among forest patches with different invasion conditions (Serrano native forest, mixed forest and glossy privet forest) using a landscape approach. We found that bird richness was substantially lower in glossy privet forests, with up to 37% loss of bird species. Bird assemblages in invaded habitats changed, with an increase in the prevalence of bird species that feed on glossy privet, particularly during the cold season, when Serrano forest plants do not fruit. Our findings show that the loss of bird diversity and structural assemblage simplification were directly related to the loss of structural complexity caused by the invasion of glossy privet. The increased abundance of birds feeding on glossy privet contributed to the spread of this plant. Given the probable continued expansion of glossy privet and its resistance to control, the persistence of diverse native bird and plant communities in areas subject to invasion by this plant species is at risk.